2019
DOI: 10.1093/toxsci/kfz039
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Glyphosate and a Glyphosate-Based Herbicide Affect Spermatogenesis in Mice

Abstract: Glyphosate is the most widely used herbicide in the world. Several studies have investigated the effects of glyphosate and glyphosate-based-herbicides (GBHs) on male reproduction, but there is still little and conflicting evidence for its toxicity. In this study, we analyzed the effects of glyphosate, alone or in formula, on the male reproductive system. Pregnant mice were treated from E10.5 to 20 days postpartum (dpp) by adding glyphosate or a GBH (Roundup ® 3 Plus) to their drinking water at 0.5 (the accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 64 publications
3
36
1
1
Order By: Relevance
“…It remains to be determined whether Glyphosate or Roundup alter the peripheral and central actions of gonadal and adrenal hormones in the mother. Previous research on human cell lines, human breast cancer cells and rodents has shown that glyphosate‐based herbicides in formulation can disrupt steroid secretion, oestrogen receptors and aromatase activity, albeit the exact mechanisms remain to be determined. The physiological and behavioural effects of glyphosate observed in the present study could be linked to endocrine disruption, and future work will aim to investigate this possibility.…”
Section: Future Directionsmentioning
confidence: 99%
“…It remains to be determined whether Glyphosate or Roundup alter the peripheral and central actions of gonadal and adrenal hormones in the mother. Previous research on human cell lines, human breast cancer cells and rodents has shown that glyphosate‐based herbicides in formulation can disrupt steroid secretion, oestrogen receptors and aromatase activity, albeit the exact mechanisms remain to be determined. The physiological and behavioural effects of glyphosate observed in the present study could be linked to endocrine disruption, and future work will aim to investigate this possibility.…”
Section: Future Directionsmentioning
confidence: 99%
“…17 Furthermore, a recent study with Swiss mice showed a reduction in plasma levels of testosterone in PND35 after maternal exposure to glyphosate alone from 10 days of gestation until the end of lactation and a reduction in sperm count after maternal exposure to glyphosate and glyphosate-ROUNDUP ® . 29 Therefore, more investigations are needed to characterize the actions of glyphosate as an EDC and its involvement in DOHaD. Herein, our hypothesis is that maternal exposure to glyphosate during the pre and postnatal period will affect the hypothalamus-pituitary-testicular axis in the F1 offspring, malprogramming the physiological development of reproductive organs during fetal and neonatal life.…”
Section: Introductionmentioning
confidence: 99%
“…17 F1 offspring from female mice exposed to GBH from gestational day 10 to PND20 also presented a decrease in sperm count and testosterone levels at PND35. 29 As such, data support the deleterious effects of maternal exposure to GBH in male offspring mice, but the specific effects on sperm count and the role of testosterone levels remain inconclusive. A testosterone surge from the testes is known to occur in neonatal rodents, which begins prenatally (at approximately embryonic day 18) and peaks on the day of birth.…”
mentioning
confidence: 99%
“…Esto implica que el glifosato puede romper al ADN y al ARN como blanco principal y secundario, respectivamente, y eventualmente puede también dañar al ATP. Estos resultados confirman lo reportado previamente sobre los daños causados en la actividad de los espermatozoides humanos debido a la acumulación de glifosato en mamíferos (Cardona-Maya, 2019;Pham et al, 2019). Los resultados obtenidos en ésta investigación muestran que las moléculas del glifosato pueden reaccionar más fácilmente con las bases nitrogenadas (interacciones 17-19 ), que incluso con otras moléculas de glifosato (interacción 16), ya que el valor del ETC es mayor en la interacción entre moléculas de glifosato que entre moléculas del glifosato y bases nitrogenadas (Tabla 2).…”
Section: Discussionunclassified